EVALUASI UJI KETURUNAN Shoreaparvifolia Dyer. UMUR 5 TAHUN DI PT SARI BUMI KUSUMA, KALIMANTAN TENGAH - Purnomo, Susilo ([Yogyakarta] : Fakultas Kehutanan UGM, 2009)
Shorea parvifolia Dyer is one of Shorea spp. and it is the most common species in the Red Meranti group. This species can grow on various ites. especially in well-drainage areas. It occurs in lowland and hill forest up to 800 m. while natural distribution ofthi~ species occurs in Southern Thailand (Pattani). P.Malaysia. Sumatra. Pusala Musala. and Borneo. Since Shorea parvifolia has grade of kelas awet about III-I V.this species is widely used as plywood and wood-construction materials. In order to supply superior materials to large-scale plantations. progeny test ofS. parvifolia is important as a part of tree improvement program. The research was conducted at five years-old S. parvifolia plantation at PT Sari Bumi Kusuma, Sei Seruyan, Central Kalimantan (00&deg